Adolescence: The Human Development between Child and Adult: Understanding the Unique Development of Children and Adolescents (Journal of Advances and Scholarly Researches in Allied Education, 2011)
The developmental processes of children and adolescents have intrigued theorists and researchers for centuries. Prior to the time of John Locke and Jean-Jacques Rousseau, during the late 17th and early 18th centuries, most people viewed children as miniature adults. During the Middle Ages children as young as six years of age were often sent off to work as apprentices in professions such as farming, blacksmithing, and carpentry. However, toward the end of the Middle Ages, the economic situation dramatically shifted; many occupations switched from requiring manual labor to necessitating academic skills. Thus, the treatment of children became refocused, away from integration with adults and toward educational instruction. In the present paper an attempt has been made to better understand that how children and adolescents are not miniature adults but unique, intriguing beings.